2009
DOI: 10.1920/wp.ifs.2009.0917
|View full text |Cite
|
Sign up to set email alerts
|

The scourge of Asian Flu: in utero exposure to pandemic influenza and the development of a cohort of British children

Abstract: This paper examines the impact of in utero exposure to the Asian influenza pandemic of 1957 upon physical and cognitive development in childhood. Outcome data is provided by the National Child Development Study (NCDS), a panel study of a cohort of British children who were all potentially exposed in the womb. Epidemic effects are identified using geographic variation in a surrogate measure of the epidemic. Results indicate significant detrimental effects of the epidemic upon birth weight and height at 7 and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 52 publications
2
69
0
1
Order By: Relevance
“…National health statistics: The physical and mental state of a person play an important role in the degree to which the individual is susceptible to a disease. It is expected that a nation composed of unhealthy individuals should also experience greater consequences of an emergent epidemics [29][30][31][32]. Specifically, metabolic disorders such as diabetes may intensify pandemic complications [33,34], whereas it has been observed that communicable diseases account for the majority of deaths in 5 complex emergencies [35].…”
Section: Socio-economic Determinantsmentioning
confidence: 99%
“…National health statistics: The physical and mental state of a person play an important role in the degree to which the individual is susceptible to a disease. It is expected that a nation composed of unhealthy individuals should also experience greater consequences of an emergent epidemics [29][30][31][32]. Specifically, metabolic disorders such as diabetes may intensify pandemic complications [33,34], whereas it has been observed that communicable diseases account for the majority of deaths in 5 complex emergencies [35].…”
Section: Socio-economic Determinantsmentioning
confidence: 99%
“…If, for instance, a child was born between October 1 and 15, then 9-6 months before birth was calculated as the total number of fatalities that occurred in their district of residence during the months of January, February, March, and April. 8 If, for instance, a child was 4 Other factors associated with low birth weight include maternal smoking (Andres and Day, 2000) and influenza infection (Kelly, 2009;Mendez-Figueroa et al, 2011;Pierce et al, 2011). Kelly (2009) found that the 1957-58 influenza pandemic in Great Britain led to decreased birth weight among children born to mothers who smoked prior to becoming pregnant and among children born to mothers who were less than 153 cm tall.…”
Section: Data and Measuresmentioning
confidence: 99%
“…8 If, for instance, a child was 4 Other factors associated with low birth weight include maternal smoking (Andres and Day, 2000) and influenza infection (Kelly, 2009;Mendez-Figueroa et al, 2011;Pierce et al, 2011). Kelly (2009) found that the 1957-58 influenza pandemic in Great Britain led to decreased birth weight among children born to mothers who smoked prior to becoming pregnant and among children born to mothers who were less than 153 cm tall. Unfortunately, the PDHS did not ask mothers about their tobacco use prior to or during pregnancy, nor did it ask about influenza infection or height.…”
Section: Data and Measuresmentioning
confidence: 99%
“…Not all of the effects of in utero exposure to influenza are identified; there are possible latent health, educational, and labor effects (Almond and Currie 2011;Kelly 2011;Schwandt 2018). For instance, using a twin, fixed-effects analysis, Black et al (2007) find that a 10 percent increase in birthweight increases the high school completion rate by a little less than one percentage point and increases full-time earnings by 1 percent.…”
Section: Limitationsmentioning
confidence: 99%